Harnessing electrostatic catalysis in single molecule, electrochemical and chemical systems: a rapidly growing experimental tool box. - Ciampi, S.; Darwish, Nadim; Aitken, H.; Díez-Pérez, I.; Coote, M. (RSC Publishing, 2018)
Static electricity is central to many day-to-day practical technologies, from separation methods in the recycling of plastics to transfer inks in photocopying, but the exploration of how electrostatics affects chemical bonding is still in its infancy. As shown in the Companion Tutorial, the presence of an appropriately-oriented electric field can enhance the resonance stabilization of transition states by lowering the energy of ionic contributors, and the effect that follows on reaction barriers can be dramatic. However, the electrostatic effects are strongly directional and harnessing them in practical experiments has proven elusive until recently. This tutorial outlines some of the experimental platforms through which we have sought to translate abstract theoretical concepts of electrostatic catalysis into practical chemical technologies. We move step-wise from the nano to the macro, using recent examples drawn from single-molecule STM experiments, surface chemistry and pH-switches in solution chemistry. The experiments discussed in the tutorial will educate the reader in some of the viable solutions to gain control of the orientation of reagents in that field; from pH-switchable bond-dissociations using charged functional groups to the use of surface chemistry and surface-probe techniques. All of these recent works provide proof-of-concept of electrostatic catalysis for specific sets of chemical reactions. They overturn the long-held assumption that static electricity can only affect rates and equilibrium position of redox reactions, but most importantly, they provide glimpses of the wide-ranging potential of external electric fields for controlling chemical reactivity and selectivity.